Symptoms related to anatomical variations of osteomeatal complex (OMC) in patients with sinonasal symptoms referred to ENT clinic of Loghman Hakim hospital between Sep 2014-Sep 2015 - Ahmady Roozbahany, Navid; Nikooseresht, Farzad (Researcher Bulletin of Medical Sciences, 2018)
Introduction: Headache or facial pain, nasal obstruction, nasal discharge, PND and hyposmia or anosmia are all symptoms of rhinosinusitis. Approximately 10% of people will experience these symptoms throughout their lives. Acute and chronic rhinosinusitis causes both symptomatic inflammation of the nasal and sinus mocusa. The role of anatomical variations of osteomedal complex (OMC) in development of these symptoms has so far been discussed. The purpose of this study is to determine the frequency of these disorders in the target population and determine their possible role in the occurrence of sinonasal symptoms. Material and Methods: This is a descriptive cross-sectional study in which patients with sinonasal symptoms referred to the ENT clinic of Loghman Hakim hospital during the period of September 2014 to September 2015 were enrolled in the study and their CT scan in the coronal view, reviewed for the existence of different anatomical variations of osteomalacial unit. Their symptoms were recorded in the table of symptoms. At the end of the study, we searched for any relation between anatomical variation of OMC and sinonasal symptoms. Results: A total of 100 patients were enrolled in the study, of which 66 were female and 34 were male. The most common symptoms in these patients were nasal obstruction 72%, headache 67%, nasal discharge 31% and hyposmia 29%. Nasal anatomical variations were also prevalent: nasal deviation 49.57%, nasal spur 25.21%, concha bollusa 23.5%, and Infraorbital cell 1.6%. Conclusion: The incidence of headache was higher in a group of patients with septal deviation than those with other anatomical variations and this difference was significantly higher in the group with septal spur and septal deviation at the same time than other anatomical variants. The incidence of nasal obstruction in patients with septal deviation and patients with septal deviation and septal spur at the same time was significantly higher than other variances. There was no statistically significant relationship with the effect of other anatomical variations on sinonasal symptoms.